Defense Mecahnims in Emily Bronte's Wuthering Heights: How Catherine Earnshaw Deal with Egocentricity - Nur Amaliyah; Yeny Prastiwi (Universitas Sanata Dharma, 2022)
This study aims to determine the personality of Catherine Earnshaw, who is the protagonist of the novel Wuthering Heights. The novel Wuthering Heights has a gothic theme and a tragedy. This novel tells the intricate love story and dominate with the social class, egoism, and hatred. The conflict is around two families namely Earnshaw and Linton. Catherine's life is filled with choices, including two loves from different people with different backgrounds and lives. That is one of reason the series of decisions and attitudes of her in the future. Catherine Earnshaw’s personality, egocentric tendencies, and defense mechanisms are the main issues in this research. This research belongs to library research which applied the qualitative research method. In addition, there are two types of data sources, namely primary data from Emily Bronte's novel Wuthering Heights and secondary data in the form of books, journals, and official sites related to research. This study applies Sigmund Freud's theory of psychoanalytic which shows three personality structures, namely the id, the ego and the superego. The results shows that Catherine Earnshaw has an egocentric tendency with five types including egocentric memory, egocentric myopia, egocentric righteousness, egocentric blindness, and egocentric immediacy. In dealing with the tendency, Catherine balances with defense mechanisms in the form of denial, identification, repression, and rationalization.